Asian consensus statements on endoscopic management of walled‐off necrosis. Part 2: Endoscopic management. Issue 9 (25th September 2016) - Isayama, Hiroyuki; Nakai, Yousuke; Rerknimitr, Rungsun; Khor, Christopher; Lau, James; Wang, Hsiu‐Po; Seo, Dong Wan; Ratanachu‐ek, Thawee; Lakhtakia, Sundeep; Ang, Tiing Leong; Ryozawa, Shomei; Hayashi, Tsuyoshi; et al.
Abstract: Walled‐off necrosis (WON) is a new term for encapsulated necrotic tissue after severe acute pancreatitis. Various terminologies such as pseudocyst, necroma, pancreatic abscess, and infected necrosis were previously used in the literature, resulting in confusion. The current and past terminologies must be reconciled to meaningfully interpret past data. Recently, endoscopic necrosectomy was introduced as a treatment option and is now preferred over surgical necrosectomy when the expertise is available. However, high‐quality evidence is still lacking, and there is no standard management strategy for WON. The consensus meeting aimed to clarify the diagnostic criteria for WON and the role of endoscopic interventions in its management. In the Consensus Conference, 27 experts from eight Asian countries took an active role and examined key clinical aspects of WON diagnosis and endoscopic management. Statements were crafted based on literature review and expert opinion, employing the modified Delphi method. All statements were substantiated by the level of evidence and the strength of the recommendation. We created 27 consensus statements for WON diagnosis and management, including details of endoscopic procedures. When there was not enough solid evidence to support the statements, this was clearly acknowledged to facilitate future research. Proposed management strategies were formulated and are illustrated using flow charts. These recommendations, which are based on the best current scientific evidence and expert opinion, will be useful for guiding endoscopic management of WON. Part 2 of this statement focused on the endoscopic management of WON.